Students’ perception on current teaching methods in clinical pharmacy courses: a focus group discussion/ Nur Natasya Ahmad Ridzuan, Shubashini Gnanasan and Mahmathi Karuppannan - Ahmad Ridzuan, Nur Natasya; Gnanasan, Shubashini; Karuppannan, Mahmathi (Faculty of Pharmacy, 2020)
This study aimed to explore students’ perception on current teaching methods used in clinical pharmacy courses and their preferred teaching methods. Fifteen fourth year pharmacy students in UiTM Puncak Alam consented and participated in this study. Three Focus Group Discussions (FGDs) were conducted which consisted of 5 students in each group. Each FGD lasted about twenty to thirty minutes and was guided by 10 semi-structured questions. Findings from FGDs highlighted four themes about students’ perceptions on current teaching methods which were beneficial for clinical skills, exposure to real practice, elevated confidence level and pitfalls of current learning structure. Students have shared various views on current teaching methods in clinical pharmacy courses along with their suggestions to improve didactic lecture and Case-Based learning (CBL) such as introducing clinical skills during third year instead of fourth year of the programme, adding extra slots for both teaching methods and changing current teaching styles. Both didactic lecture and CBL have their own advantages and disadvantages from students’ perspective. The fourth-year pharmacy students would prefer CBL than didactic lecture but agreed that combination of teaching methods will enhance their clinical skills. The results from this research can serve as a guide to improve the current curriculum in pharmacy programme and for lecturers to evaluate their current teaching methods.